A Comparative Study of the Curriculum of Undergraduate Nursing Education in Iran and Selected Renowned Universities in the World - Esmat Noohi; Leila Ghorbani-Gharani; Abbas Abbaszadeh (Kerman University of Medical Sciences, 2015)
Background & Objective: In order to achieve more success in the Bachelor of Science in the discipline of nursing education in Iran and identify its weaknesses and strengths comparative studies and utilization of successful universities strategies and experiences are necessary The present research compares the curricula of undergraduate nursing education in Iran and 8 selected universities from America Europe Australia and Asia The universities were compared in terms of student selection methods mission and objective general structure program length educational content teaching and learning methods educational strategies role of graduates and evaluation methodologies Methods: This was a descriptivecomparative study In the present study 8 renowned and innovative nursing schools were selected through purposeful sampling method The important components and indices of nursing curricula of the 8 nursing schools in America Europe Australia and Asia were analyzed Then each studied item was compared between the selected nursing schools and nursing schools of Iran Practical suggestions were made to improve the quality of the nursing curriculum in Iran in terms of improvement of each studied item The research model used in this study was the Beredy model that identified the 4 stages of description interpretation proximity and comparison in comparative studies Results: The general objectives and educational contents in all curricula of the examined nursing schools were to some extent similar However the establishment and development of the contents and the method extent and type of addressing them were different These differences created different contents Moreover despite the many similarities in training and evaluation techniques many differences depending on the level and purpose of the program were observed Conclusion: It seems that although the nursing curriculum in Iran does not hold a dissatisfactory position in comparison with the other studied curricula in order to resolve the flaws items like goals selection student selection methods research teaching and evaluation (theory and performance) methodologies need to be reviewed and revised